Estudio de pre-factibilidad para la creación de una empresa de transporte terrestre de carga pesada Tunja (Boyacá (2021)
The purpose oft his to carry out a pre-feasibility study for the creation of a heavy load transport company, located in the municipality of Tunja in the Department of Boyacá witht the aim of establishing its viability, recognizing the opportunities and advantages that this stype service can offer throughout the region.